Rare manifestations of Potter Sequence: A Case Report - Gautam, Uttara (JNMA J Nepal Med Assoc, 2020)
Potter sequence is a rare congenital malformation that primarily affects male fetuses and is characterized by pulmonary hypoplasia, skeletal malformation, and kidney abnormalities. The pressure of the uterine wall due to oligohydramnios leads to an unusual facial appearance, abnormal limbsor limbs in abnormal positions or contractures. The fetus generally dies soon after birth due to respiratory insufficiency. We presented a male baby of 35 wks gestation with birth weight 1200gms delivered by primi mother. She had severe oligohydramnios and virtually there was no liquor during birth. The baby had severe perinatal depression at birth requiring resuscitation. Multiple congenital anomalies like absence of left eye, congenital cataract on the right eye, right-sided choanal atresia, micrognathia, low set ears, beaked nose, bilateral clubbed foot with hip deformity were noted. After 2 hours of life,baby developed fast breathing and cyanosis and died due to respiratory failure.